The design, development and evaluation of a biomass-fueled cabinet dryer for high-quality cassava flour production - Adegbite, S.; Asiru, W.; Okewole, O.; Awoyale, W.; Kolawole, P.; Diallo, T.; Abass, A. (2025)
Cassava is an essential staple crop in developing nations, ensuring food security and generating income for smallholder farmers. The lack of modern drying technology in rural regions requires effective strategies to reduce post-harvest losses and improve product quality. This study introduces a biomass-powered cabinet dryer designed to produce high-quality cassava flour (HQCF), featuring a heat exchanger, blower, and drying chamber constructed from locally sourced materials. The drying chamber contains two racks, each equipped with 10 trays, accommodating 40 to 80 kg of wet cassava mash per batch. The dryer, operating at temperatures between 50 and 115 °C for a duration of 10–120 min, decreased moisture content from 38.21% to around 11%. Drying efficiencies varied from 59.22% to 88.24%, whereas biomass efficiencies ranged from 3.0% to 4.0%. The results demonstrate the dryer’s efficiency in drying, while the study emphasizes the necessity of customized technical solutions to assist rural populations in cassava-producing areas.